Modified haemagglutination inhibition assay for the detection of canine parvovirus type 2 antibodies in dog sera. (August 2021) - Cavalli, A.; Martella, V.; Desario, C.; Camero, M.; Lanave, G.; Barrs, V.R.; Decaro, N.; Buonavoglia, C.
Highlights: Evaluation of passive immunity facilitates effective vaccination in puppies. A haemagglutination inhibition assay was modified to improve interpretation. Pre-treatment of sera with red blood cells prevented nonspecific hemagglutination. Lowering the concentration of red blood cells prevented artefactual precipitation. Abstract: Canine parvovirus type 2 (CPV-2) infection is associated with severe gastroenteritis in puppies. Quantification of CPV-2 specific antibodies before vaccination can reveal the presence of interfering maternal-derived immunity and facilitate timing of effective immunisation. Inhibition of haemagglutination (HI) is commonly used to measure CPV-2-specific antibody levels in serum. However, the presence of nonspecific agglutinins in canine serum and artefactual precipitation of red blood cells (RBC) are both limitations of the assay. In this study, we compared the standard HI protocol with a refined HI protocol, in which canine serum was pre-incubated with porcine RBC for 12 h to remove nonspecific agglutinins and a lower concentration (0.1% vs. 0.8%) of porcine RBC suspensions was used to limit artefactual precipitation of RBC. A panel of canine sera, collected from 80 dogs of different ages and with different neutralising antibody titres, was analysed. Nonspecific agglutinins were identified in most (97%) serum samples from puppies <4 months of age and in only 7% dogs 6 months old. Pre-treatment of serum samples was effective in removing nonspecific agglutinins from all samples and artefactual precipitation of RBCs was not noted when 0.1% RBC suspensions were used. Refinement of the HI protocol has increased the accuracy of interpretation and reduced the interference of nonspecific agglutinins, primarily seen in puppies. This reduces the likelihood of incorrect assessment of passive or active immunity in puppies when deciding whether to administer or defer vaccination, which could potentially leave them susceptible to CPV-2 infection.